1897 Idaho Sess. Laws 89 - (:unkn) unknown (My University, 1897)
§ 2, pt. 18: Amended the Boise city charter to authorize the storage and sale of gun powder and other combustible materials, as well as "all possible and proper means" to prevent the danger or risk of injury or damage by fire from carelessness, negligence, or otherwise.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER